FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GANGGUAN FUNGSI PARU PADA POLISI LALU LINTAS DI SATLANTAS POLRESTABES SEMARANG - Amaliyah, Ratu Aam; Setiani, Onny; Dangiran, Hanan Lanang (Jurnal Kesehatan Masyarakat (Undip), 2018)
Urban air pollution is caused by the presence of particulate matter. The result of total dust measurement in 2017 at Simpang Lima and Dr. Sutomo’s street was 136 µgr/Nm3 and 141 µgr/Nm3. Traffic policeman are proffesions that are susceptible to lung function impairment due to frequent exposure to pollutant substances from road dust. The purpose of this study was to know the association between total dust, work period and use of PPE and lung function disorder on traffic policeman Satlantas Polrestabes Semarang. The type of study was observasional analytic with cross sectional design. The total samples were 37 respondens who spread across 5 police post. Data were collected by interviews, measurements of total dust by using High Volume Air Sampler (HVAS) and measurements of lung capacity by using spirometer. Data analysis was conducted with spearman correlation test for temperature variable with total dust variable and chi square test for total dust, work period and use of ppe with lung function disorder. The result of study showed that there were 16 people with lung function disorder (43,2%). There were no association between total dust concentration and lung function disorder (p=0,255>0,05). There were no association between work period and lung function disorder (p=0,571>0,05). There were association between use of PPE and lung function disorder (p=0,02<0,05). The conclusion of this study there is an association between the usage of PPE and  lung function disorder on traffic policeman Satlantas Polrestabes Semarang.